Preferência condicionada a psicoestimulante em ratos jovens após suplementação com diferentes ácidos graxos - Kuhn, Fábio Teixeira (2013)
Western diet has undergone major changes in recent decades, mainly due to the large consumption of processed foods and fast foods, which contains a large proportion of fats rich in trans fatty acids (TFA). Polyunsaturated fatty acids (PUFA) are essential components of the neuronal membranes, and the main PUFAs are the omega-3 series (n-3) and omega 6 (n-6), which are obtained solely from the diet. Trans fatty acids (TFAs) can inhibit the activity of enzymes such as desaturases and elongases, and also compete with PUFA for incorporation into neuronal membranes, modifying its fluidity and affecting physiological functions in neurochemical brain. The quality of fat consumed during periods of pregnancy and lactation determines a significant transfer of PUFA and TFA through the placenta and breast milk. Different mechanisms related to the change in composition of fatty acids can cause behavioral changes which can especially be reflected on dopaminergic neurotransmission, thus increasing anxiety and hedonia, which may exacerbate the additive effect of psychostimulant drugs. Adolescence is the period in which there is a great novelty seeking, which increases the likelihood for early experiences that may culminate in addition. The protocol conditioned place preference (CPP) is a widely used animal model for understanding the mechanisms involved in the abuse of psychoactive drugs, also serving as a research tool, enabling the prevention and/or treatment of addiction. The aim of this study was to evaluate the influence of supplementation of different fats rich in n-3 fatty acids (fish oil-FO), n-6 (soybean oil-SO) and trans fatty acids-TFA (hydrogenated vegetable fat-HVF) since pre-conception, pregnancy and lactation, and maintained until adolescence on anxiety parameters and preference to amphetamine (AMPH) in young rats, which were evaluated with analyzes of cerebral oxidative status. During 6 weeks, 24 female Wistar rats were supplemented with SO, FO and HVF, comprising the periods from conception, pregnancy until the end of breastfeeding. After weaning, only 1 male puppy from each litter was separated and kept with the original supplementation until 40 days of age when they were subjected to the conditioning protocol (8 days) with AMPH to conduct behavioral and biochemical tests. HVF increased conditioned place preference by AMPH and showed anxiety-like symptoms during withdrawal, indicating a greater potential for abuse in this experimental group. The HVF supplementation during development and growth was also associated with higher oxidative damage and reduced antioxidant activity, while the FO supplemented group showed lower protein carbonyls. This study showed the deleterious influence of consumption of TFA during the perinatal period and during development, which can be evidenced by symptoms especially preference at psychostimulants, anxiety and oxidative damage in the brain.